2016
DOI: 10.1186/s12873-016-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal ketamine for acute traumatic pain in the Emergency Department: a prospective, randomized clinical trial of efficacy and safety

Abstract: BackgroundKetamine has been well studied for its efficacy as an analgesic agent. However, intranasal (IN) administration of ketamine has only recently been studied in the emergency setting. The objective of this study was to elucidate the efficacy and adverse effects of a sub-dissociative dose of IN Ketamine compared to IV and IM morphine.MethodsA single-center, randomized, prospective, parallel clinical trial of efficacy and safety of IN ketamine compared to IV and IM morphine for analgesia in the emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…These reactions may be due to the bitter taste of ketamine, which could have caused irritation and an unpleasant sensation in the dogs. In human medicine, patients receiving intranasal ketamine frequently complain about a bad taste in the mouth, due to drug runoff into the pharynx [6,9,13,59].…”
Section: Dogmentioning
confidence: 99%
See 1 more Smart Citation
“…These reactions may be due to the bitter taste of ketamine, which could have caused irritation and an unpleasant sensation in the dogs. In human medicine, patients receiving intranasal ketamine frequently complain about a bad taste in the mouth, due to drug runoff into the pharynx [6,9,13,59].…”
Section: Dogmentioning
confidence: 99%
“…In addition, intranasal drug delivery avoids painful parenteral administration. Intranasal ketamine has been successfully used for sedation and premedication of pediatric patients [5][6][7] and in pain management of both children and adults [8][9][10][11][12][13]. Another application lies in psychiatry, where intranasal ketamine has been shown to be safe and effective for the treatment of major depressive disorders [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Ketamin, tek başına veya geleneksel opioidlerle birlikte etkindir. Damar yolu sağlanamamış hastalarda intranasal ketamin de yeğlenebilir (41) . HKA ağrı kontrolü için iyi bilinen bir tekniktir.…”
Section: Analjeziunclassified
“…At high doses drug causes hallucination, disturbed sleep, increased intracranial pressure, high blood pressure, tachycardia, and tonic-clonic seizure [7]. Several studies have shown that ketamine is effective agent in the treatment of pain [8] and morphine is the most commonly used analgesic in emergency centers [5,[9][10][11][12][13][14][15][16]. Intravenous ketamine is an available agent associated with minimal complications and side effects while the morphine is less available and associated with several side effects such as tolerance [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%